Minimum wage - a necessity or a superfluous thing? - Borkowski, Christopher (International Journal of Accounting and Economics Studies, 2017)
The article moves the issue of the minimum wage, its significance and the meaning of existence on the social level. There have been discussions over the issue over the years, with many supporters of the minimum wage as well as its opponents. The subject can be considered in many respects - macroeconomic, microeconomic, financial, but primarily social. The author presents, what impact has the existence of a minimum wage on a man, especially a young man who has just finished education and answers the questions: whether the discrepancies in earnings are a normal thing? Whether the minimum wage can affect the reduction of social stratification in earnings? It also shows the concept of fair wage and using modern methods of measuring human capital shows that it is possible to calculate the level of minimum wage for pay. In the next section, it compiles the calculated minimum wage levels in each country, together with the minimum wage that is in effect. By analyzing all the possibilities, the author concludes that the existence of a minimum wage is essential for the proper functioning of society as well as for the economy of a whole. However, it is a prerequisite to set it at the right level, not too low and not too high, which in theory is feasible, but in reality, practically impossible, but still cannot stop efforts and constantly update the value of the minimum wage to be as close as possible to the optimal value.